Efficient construction of rAAV-based gene targeting vectors by Golden Gate cloning. (May 2014) - Luo, Yonglun; Lin, Lin; Bolund, Lars; Sørensen, Charlotte Brandt
The recombinant adeno-associated virus (rAAV) has proven to be an efficient and attractive tool for targeted genome engineering. Here we present a novel method employing the Golden Gate cloning strategy for fast and efficient construction of rAAV-based gene knockout or single-nucleotide knockin vectors. Two vectors, pGolden-Neo and pGolden-Hyg, were generated as common assembling modules to confer antibiotic resistance to the targeting vector. To validate the method, we then generated two rAAV-based targeting vectors: pAAV-pTP53-KO and pAAV-hTauP301L-KI. Furthermore, we generated a pGolden-AAV plasmid that allows one-step generation of an rAAV-based targeting vector. Our new methodology for rAAV targeting vector assembly is efficient, accurate, time-saving, and cost-effective.